Habitat preference based on herpetofauna spatial distribution in Coal Mining Area of PT Singlurus Pratama, East Kalimantan - Teguh Muslim; Yaya Rayadin, Ali Suhardiman (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2018)
Herpetofauna communities are formed due to the suitability of the habitat or adaptation process that forces a species to survive. The opening of the land mines result in missing or changing the habitat of herpetofauna. This research was conducted to know the preferences of the herpetofauna of habitat based on spatial distribution of herpetofauna in the vicinity of mining area of PT Singlurus Pratama. The survey was conducted in the area of revegetasi, forest fragmentation, the district adjacent to the mining area, rivers and water spots or natural and man-made on two mining blocks i.e. block Pearl and block independence. The method of election of purposive sampling location with direct search survey methods (Visual Encounter Surveys). The main species found 4 that its spread most widely with populations high. The most frequent species of herpetofauna and many found among others: Eutropis multifasciata, Enhydris enhydris, Fejervarya cancrivora, Polypedates leucomystax and Duttaphrynus melanostictus. Based on the value of the index indicates that the diversity of herpetofauna communities distress with low. Types of herpetofauna more land cover found in the undergrowth, secondary forest and agricultural areas that there are sources of water in it.